Próba zastosowania lotniczych termowizyjnych obrazów wideo do wykrywania miejsc nielegalnego składowania odpadów zwierzęcych - Kijowski, Andrzej; Mania, Wojciech (My University, 2009)
Access to the remote sensing data was increasing in Poland since 1989. This procccess had stimulating impact on scientific research in the scope of changes in the environment. Special attention should be given to the thermal imagery methods because of its information potential. Presented paper discusses the possibilities of using information from thermal images for detecting of places of illegal dumping of animal waste in the ground. On the basis of earlier survey and gathered data draft fl ight plan was created, covering the sorroundings of Śmiłowo (around 30 sq km). Theoretical thesis for the subject was an assumption that all disturbances of the ground and soil structure should give visible representation in both thermal and visible images. Moreover the process of decay of animal tissues should be the source of heat, which can be observed through thermal sensor. Several places of potential dumping of animal waste were selected. For detailed ground verifi cation eight of them were chosen. In these location geological drillings were performed and than analysis of the samples. Thermovision is a method with great potential for the monitoing of the environment, but its effectiveness depends on the access to another sources of geoinformation.
Attempt of using aerial thermal video images for detecting places of illegal dumping of animal waste
Keywords: lotnicze obrazy termowizyjne; odpadów zwierzęcych; aerial thermal video images; animal waste